Identification of S-nitrosylated proteins in postmortem pork muscle using modified biotin switch method coupled with isobaric tags. (November 2018) - Liu, Rui; Fu, Qingquan; Lonergan, Steven; Huff-Lonergan, Elisabeth; Xing, Lujuan; Zhang, Lili; Bai, Yun; Zhou, Guanghong; Zhang, Wangang
Abstract: The objective of this study was to identify the S-nitrosylated proteins in aging samples of pork longissimus thoracis muscle (aged 0 and 3 d) and to study the effects of exogenous S-nitrosoglutathione (GSNO, concentration at 10 and 100 μM) treatments of aged 0 d sample. After validating modified biotin switch method, the samples were labeled with tandem mass tags (TMT126-129) for the LC-MS/MS analysis. A total of 366 peptides were identified to be S-nitrosylated corresponding to 339 proteins. Comparison of total intensity and individual S-nitrosylated sites between aging samples revealed that S-nitrosylation did occur in pork muscle during postmortem aging through possible pathways of denitrosylation and transnitrosylation. GSNO treatment groups showed a considerable number of potential cysteines could be modified with high thiol-reactivity. It was deduced that S-nitrosylation could be involved in the postmortem metabolic process possibly through the regulation of activity or function of glycolytic enzymes, calcium release, heat shock proteins, antioxidant enzymes and myofibrillar proteins. Highlights: S-nitrosylated proteins in postmortem aging of 0 and 3 d was identified. Isobaric tandem mass tag (126–129) was used to multiplex quantification. Denitrosylation and transnitrosylation may occur in postmortem aging. Thiol-reactivity of S-nitrosylation was detected by exogenous GSNO treatment. Identified S-nitrosylated proteins have implications in metabolism during aging.